1996
DOI: 10.1051/aas:1996295
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal structures in the wind and chromosphere of the Herbig Ae star AB Aurigae. Results from the MUSICOS 1992 campaign

Abstract: Abstract. -The observations of the MUSICOS 1992 campaign concerned three scientific programs, among which was the study of azimuthal structures in the wind and chromosphere of the pre-main sequence Herbig Ae star AB Aur. The He 15876 Â line of AB Aur, which is formed in the expanding chromosphere of this star, most probably in the innermost parts of its wind, was continuously monitored at a spectral resolution of 30000 for about 4 days. The line was discovered to be variable in a spectacular way, the profile c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Asteroseismology represents a modern tool for studying the stellar interiors of the enigmatic group of pre-main sequence (PMS) stars of intermediate mass (∼ 2-8 M ⊙ ), so called Herbig Ae/Be stars (Herbig, 1960;Strom et al, 1972;Finkenzeller & Mundt, 1984;Finkenzeller & Jankovics, 1984). Since their first systematic classification in 1960 (Herbig, 1960) this group of young stars has been extensively studied, but one of the major questions remains unanswered: how can the intense stellar activity and strong stellar winds (Praderie et al, 1982;Catala & Kunasz, 1987;Böhm &Catala, 1995 andBöhm et al, 1996), as well as the many highly variable emission lines observed in the spectra of these stars be explained?…”
Section: Introductionmentioning
confidence: 99%
“…Asteroseismology represents a modern tool for studying the stellar interiors of the enigmatic group of pre-main sequence (PMS) stars of intermediate mass (∼ 2-8 M ⊙ ), so called Herbig Ae/Be stars (Herbig, 1960;Strom et al, 1972;Finkenzeller & Mundt, 1984;Finkenzeller & Jankovics, 1984). Since their first systematic classification in 1960 (Herbig, 1960) this group of young stars has been extensively studied, but one of the major questions remains unanswered: how can the intense stellar activity and strong stellar winds (Praderie et al, 1982;Catala & Kunasz, 1987;Böhm &Catala, 1995 andBöhm et al, 1996), as well as the many highly variable emission lines observed in the spectra of these stars be explained?…”
Section: Introductionmentioning
confidence: 99%
“…In the future, much attention must be paid to the suggestions made by Thomas [87] and the references therein concerning the properties of atmospheres of active stars having, in addition to the atmospheric structures modified by the rapid rotation, a more or less permanent supply of non-thermal energy by the sources of hydrodynamic and magnetic nature, to better understand the internal structure of these objects. Up to now, instead, few authors have studied the consequences produced by the deviations from the classical thermal structure of stellar atmospheres on the emitted spectra, e.g., [88][89][90][91][92][93][94][95][96].…”
Section: Disc-shaped Envelopes In Be Stars Just a Few Remindersmentioning
confidence: 99%
“…Short-term variability of many of these lines are observed and P Cygni profiles of Hα, Hβ, Mg II h and k lines present in the spectra of some of these stars indicate the presence of strong and structured stellar winds (see e.g. Praderie et al 1982Praderie et al , 1986Catala & Talavera 1984;Catala et al 1986a,b;Catala & Kunasz 1987;Catala 1988;Böhm & Catala 1995;Böhm et al 1996).…”
Section: Introductionmentioning
confidence: 99%